Estudo da corrosão do aço ao carbono em meio de sulfeto - Zimer, Alexsandro Mendes (2009)
This work presents a study of the 1020 and 1040 carbon steel corrosion in aqueous solution containing dissolved H2S in order to investigate the effect of H2Saq and HSaq species. Some different electrolytes were used: acetic acid buffer and phosphate buffer in presence or absence of 3.5 wt% NaCl solution containing 10, 25, 50, 100, 200, 500, 1000 and 2000 ppm of Na2S. The corrosion steel was described by means electrochemical impedance spectroscopy (EIS), potential polarization curves (PC), open circuit potential (Eoc) and in situ optical microscopy. Other experiments were carried out seeking to understand the steel corrosion process in sulfide solution. Thus, the influence of the 4 factors together (sulfide species, concentration, presence of chloride and steel type) was assessed by the interpretation of interactions and main effects in an experiments using factorial design. The characterization of the films was performed by electrochemical impedance spectroscopy in situ and ex situ techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The EIS measurements showed two distinct regions, high and low frequencies and the data analysis as a combination of diffusion and charge transference resistance, capacitances and constant phase elements (CPE). This parameters allow studying the corrosion of iron in presence of different sulfide species. The influence of total H2S concentration as well as the effect of immersion time on the corrosion was investigated too. In presence of the H2S the Rct values increase initially with immersion time but then decrease gradually. We concluded that there is formation of a protective film that reaches its maximum thickness after 3 h, and this layer is later dissolved to grow back again until reaching an equilibrium value at immersion time over 10 h. If the sulfide films has many porous, the capacitance presents high values to the corrosion process. In this case the number of defects of the sulfide films is proportional to increasing of corrosion. For the factorial design it was concluded that the species of sulfide is the most relevant factor for the corrosion process, followed by concentration and the presence of chloride in the solution. In the presence of H2S happens to active dissolution of iron and in the presence of HS- can occur the formation of a protective film. By images of in situ optical microscopy, carried out during the electrochemical measurements, one can observe the dissolution of ferrite in the pearlitic region and a formation of iron sulfide films with different colors. Morphological analysis and classification of surface corrosion damage, carried out by digital processing of images, show that happens grain-boundaries corrosion, pitting corrosion and formation of sulfide film initially over pearlitic grains.